Barton Creek - BRIT Press (Journal of the Botanical Research Institute of Texas, 2019)
Ed Crowell. 2019. Barton Creek. (ISBN-13: 978-1-62349-729-3, flexbound with flaps). Texas A&M University Press, John H. Lindsey Building, Lewis St., 4354 TAMU, College Station, Tex-as 77843, U.S.A. (Orders: www.tamupress.com). 27.00 US, 140 pp., 63 color photos, 4 b&w photos, map, bibliography, index, 9" × 10".